The culture of beet in no-tilling under different corn straw densities (Research, Society and Development, 2023)
The beet (Beta vulgaris L.) belonging to the Amaranthaceae family is one of the main vegetables produced in Brazil. New cultivation and soil preparation techniques are being used, including the SPDH (Direct Planting System for Vegetables). Thus, the objective of the present work was to evaluate the incidence of weeds, the diversity of insects, and the development of beet in a no-tillage system with different densities of corn straw. The experiment was carried out in the municipality of Nova Laranjeiras (PR) in a vegetable no-tillage system, using maize at different densities (0, 40, 60, 80 and 100 thousand plants/ha) as soil cover, the cultivar of Early Wonder Tall Top Beetroot. The experimental design used was in interspersed blocks in a factorial scheme. The evaluated variables were water retention capacity, soil basal respiration, straw decomposition index, height of the aerial part, number of leaves and survival index of beet plants, incidence of phytophages and phytopathogens and the survey of spontaneous plants. Data underwent analysis of variance (ANOVA) and significant data were compared at 5% probability, regression analysis and Tukey's test were performed. The results of water retention capacity, soil basal respiration and incidence of weeds were significant for the evaluated densities and periods. It concludes that the use of corn cover on beet beds reduced the incidence of weeds, but reduced beet establishment by 30%.